1995
DOI: 10.1016/s0006-3495(95)80211-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quantitative calcium flux through NMDA, ATP, and ACh receptor channels

Abstract: NMDA receptors, ATP receptors, and nicotinic ACh receptors respond to agonist by undergoing conformational changes that open weakly selective cationic channels that are permeable to calcium. We determined the fraction of the current carried by calcium by simultaneously measuring membrane current using whole-cell patch-clamp techniques and intracellular Ca2+ using the fluorescent indicator Fura-2. The Fura-2 response to free Ca2+ was calibrated individually for each cell. Two different calibration methods are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
77
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(87 citation statements)
references
References 37 publications
9
77
0
1
Order By: Relevance
“…The calcium permeability of ganglion-type nicotinic receptors is reported to be similar to that of adult muscle in experiments on superior cervical ganglion, intracardiac ganglia and chromaffin cells, with values for calcium permeability (relative to sodium or caesium) between 0.5 and 1 and fractional current measurement between 2.5 and 4.7% (Fieber & Adams, 1991;Zhou & Neher, 1993;Vernino et al, 1992;Vernino et al, 1994;Nutter & Adams, 1995;Rogers & Dani, 1995). This is in broad agreement with recombinant work on heteromeric receptors or native receptors likely to be heteromeric (Mulle et al, 1992a;Costa et al, 1994;Ragozzino et al, 1998).…”
Section: Biophysical Properties Calciumsupporting
confidence: 74%
“…The calcium permeability of ganglion-type nicotinic receptors is reported to be similar to that of adult muscle in experiments on superior cervical ganglion, intracardiac ganglia and chromaffin cells, with values for calcium permeability (relative to sodium or caesium) between 0.5 and 1 and fractional current measurement between 2.5 and 4.7% (Fieber & Adams, 1991;Zhou & Neher, 1993;Vernino et al, 1992;Vernino et al, 1994;Nutter & Adams, 1995;Rogers & Dani, 1995). This is in broad agreement with recombinant work on heteromeric receptors or native receptors likely to be heteromeric (Mulle et al, 1992a;Costa et al, 1994;Ragozzino et al, 1998).…”
Section: Biophysical Properties Calciumsupporting
confidence: 74%
“…These findings suggest that the nAChRs show higher relative permeability to calcium than their muscle counterpart (Vernino et al, 1992) and can, in some cases, like that for the ␣7-containing nAChRs, be comparable to that seen for the NMDARs, the current benchmark for a calcium-permeable receptor. From direct measurements of calcium flux using fluorescence calcium indicators, it is estimated that calcium contributes to about 4 -5% of the total current carried by ␣Bgt-insensitive nAChRs (Vernino et al, 1994;Rogers and Dani, 1995). Such measurements have not been performed on nAChRs containing the ␣7 subunit, but in neurons, flux through these nAChR subtypes might be sufficient to modulate neurotransmitter release (Gray et al, 1996).…”
Section: Calcium Flux Through Nachrsmentioning
confidence: 99%
“…Finally, ␣7 nAcChoRs are believed to be highly Ca 2ϩ permeable (9,(22)(23)(24)35); because of the very wide range of actions played by intracellular Ca 2ϩ , a study of Ca 2ϩ permeability will help us to understand the physiopathological role of ␣7-containing nAcChoRs in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5], and it is now well established that Ca 2ϩ may permeate the pore of various types of neurotransmitter-gated receptors in the brain. Nevertheless, direct determinations of the transmitter-activated Ca 2ϩ inflow lacked until the Ca 2ϩ entry into the cells was monitored by a combination of electrophysiological and optical techniques with Ca 2ϩ sensitive dyes (6)(7)(8)(9)(10)(11)(12). While trying to measure Ca 2ϩ influx through nicotinic receptors, we and others found that the adult muscle nAcChoR channel is much more permeable than the embryonic muscle nAcChoR (11,13) but less permeable than some neuronal nAcChoR channels (7,11,14).…”
mentioning
confidence: 94%